Pestalotiopsis abietis sp. nov. from Abies fargesii in China - Gu, Mo; Hu, Dong-Wei; Han, Bing; Jiang, Ning; Tian, Cheng-Ming (Phytotaxa, 2021)
Pestalotiopsis is a common genus worldwide and causes diseases on many plant hosts. During our investigation on plant diseases in Qinling Mountain in China, Pestalotiopsis species on needles of Abies fargesii was discovered. Based on the phylogeny of combined ITS, TEF and TUB genes, three Pestalotiopsis isolates from present study cluster into a distinct clade close to P. parva in the genus. However, conidia of Pestalotiopsis abietis are obviously larger than those from P. parva. Hence, Pestalotiopsis abietis sp. nov. is introduced herein.